Comparative transcriptome analysis of nodules of two Mesorhizobium–chickpea associations with differential symbiotic efficiency under phosphate deficiency. (4th August 2017) - Nasr Esfahani, Maryam; Inoue, Komaki; Chu, Ha Duc; Nguyen, Kien Huu; Van Ha, Chien; Watanabe, Yasuko; Burritt, David J.; Herrera‐Estrella, Luis; Mochida, Keiichi; Tran, Lam‐Son Phan
Summary: Phosphate (Pi) deficiency is known to be a major limitation for symbiotic nitrogen fixation (SNF), and hence legume crop productivity globally. However, very little information is available on the adaptive mechanisms, particularly in the important legume crop chickpea ( Cicer arietinum L.), which enable nodules to respond to low‐Pi availability. Thus, to elucidate these mechanisms in chickpea nodules at molecular level, we used an RNA sequencing approach to investigate transcriptomes of the nodules in Mesorhizobium mediterraneum SWRI9–( Mm SWRI9)–chickpea and M .  ciceri CP‐31–( Mc CP‐31)–chickpea associations under Pi‐sufficient and Pi‐deficient conditions, of which the Mc CP‐31–chickpea association has a better SNF capacity than the Mm SWRI9–chickpea association during Pi starvation. Our investigation revealed that more genes showed altered expression patterns in Mm SWRI9‐induced nodules than in Mc CP‐31‐induced nodules (540 vs. 225) under Pi deficiency, suggesting that the Pi‐starvation‐more‐sensitive Mm SWRI9‐induced nodules required expression change in a larger number of genes to cope with low‐Pi stress than the Pi‐starvation‐less‐sensitive Mc CP‐31‐induced nodules. The functional classification of differentially expressed genes (DEGs) was examined to gain an understanding of how chickpea nodules respond to Pi starvation, caused by soil Pi deficiency. As a result, more DEGs involved in nodulation, detoxification, nutrient/ion transport, transcriptional factors, key metabolic pathways, Pi remobilization and signalling were found in Pi‐starved Mm SWRI9‐induced nodules than in Pi‐starved Mc CP‐31‐induced nodules. Our findings have enabled the identification of molecular processes that play important roles in the acclimation of nodules to Pi deficiency, ultimately leading to the development of Pi‐efficient chickpea symbiotic associations suitable for Pi‐deficient soils. Significance Statement: Phosphorous is an essential nutrient for plants, and plant roots absorb phosphorus from soils only in the form of phosphate (Pi). Low‐Pi availability is one of the major constraints limiting symbiotic nitrogen fixation, thereby legume productivity. Thus, it is critical to gain an in‐depth understanding of the molecular basis of how nodules respond to Pi deficiency and to identify Pi‐responsive genes, whose expression could be manipulated to enable optimal growth of legumes under low‐Pi conditions.